2019
DOI: 10.1007/s00330-019-06401-7
|View full text |Cite
|
Sign up to set email alerts
|

Second-look PET-CT following an initial incomplete PET-CT response to (chemo)radiotherapy for head and neck squamous cell carcinoma

Abstract: This is a repository copy of Second-look PET-CT following an initial incomplete PET-CT response to (chemo)radiotherapy for head and neck squamous cell carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 26 publications
1
13
1
Order By: Relevance
“…In our cost‐utility model, novel PET‐CT surveillance was the dominant strategy across a wide range of variables compared with traditional PET‐CT, likely as a result of a 40% lower neck dissection rate. Novel and standard PET‐CT strategies showed similar survival and locoregional control, consistent with the findings of other studies 6‐8 . Our findings corroborate the value of a stepwise approach with a second PET‐CT in equivocal responders.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…In our cost‐utility model, novel PET‐CT surveillance was the dominant strategy across a wide range of variables compared with traditional PET‐CT, likely as a result of a 40% lower neck dissection rate. Novel and standard PET‐CT strategies showed similar survival and locoregional control, consistent with the findings of other studies 6‐8 . Our findings corroborate the value of a stepwise approach with a second PET‐CT in equivocal responders.…”
Section: Discussionsupporting
confidence: 90%
“…Consequently, newer studies have advocated for the use of an interval PET‐CT scan to improve the diagnostic performance of PET‐CT and reduce the rate of false positives leading to unnecessary neck dissection. Prestwich et al 7 evaluated patients with head and neck squamous cell carcinoma who underwent an interval PET‐CT performed roughly 3 months after the initial 3‐month posttreatment scan of patients with an incomplete/equivocal response. On interval PET‐CT, they found that 74% patients with initial incomplete/equivocal response converted to a complete nodal response.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Porceddu et al recommend a further repeat PET-CT 4-6 weeks later (16 weeks post treatment) if the first one shows indeterminate response, with no subsequent cases of nodal failure 12 . Similarly a recent publication from our group highlighted that a second-look PET-CT 13 weeks median duration from the first response assessment PET-CT (median 30 weeks post treatment) found the majority of incomplete response cases convert to a complete metabolic response 30 . Follow-up imaging at an earlier time point results in a higher number of false positive results 31 .…”
Section: Discussionmentioning
confidence: 58%